Review of the Balkan Isophya (Orthoptera: Phaneropteridae) with particular emphasis on the Isophya modesta group and remarks on the systematics of the genus based on morphological and acoustic data - Chobanov, Dragan P.; Grzywacz, Beata; Iorgu, Ionuţ Ş.; Cιplak, Battal; Ilieva, Maya B.; Warchałowska-Śliwa, Elżbieta (Zootaxa, 2013)
A critical review of the taxonomy and systematics of the genus Isophya from the Balkan Peninsula, together with a revision of the I. modesta group, including its representatives outside the Balkans, has been made using morphological, bioacoustic and karyological data. As a result, the following taxonomic considerations have been proposed: (1) the status of two taxa has been reconsidered: Isophya rhodopensis leonorae Kaltenbach, stat.n., I. rhodopensis petkovi Peshev, stat.n.; (2) five synonymies have been established: I. hospodar (Saussure) = I. hospodar medimontana Nedelkov, syn.n.; I. plevnensis Peshev, sensu novo = I. pravdini pravdini Peshev, syn.n.; I. rhodopensis leonorae Kaltenbach = I. kisi Peshev, syn.n.; I. obtusa = I. pravdini bazyluki Peshev, syn.n.; I. modesta Frivaldszky = I. modesta intermedia Kis syn.n. The descriptions of the taxa under consideration are supplemented with unpublished morphological and/or bioacoustic data. An updated list of the taxa occurring on the Balkans includes 24 taxa (21 species, including the doubtful data on I. camptoxypha). A dichotomic and tabulated key for recognition and maps of distribution of the established taxa are presented.